Book Review: Ruggiero, Diana (2022). Teaching World Languages for Specific Purposes: A Practical Guide. Georgetown University Press, pp. 121 - Jeffrey Killman (Revista de Lenguas para Fines Específicos, 2023)
In Teaching World Languages for Specific Purposes: A Practical Guide, the author, Diana Ruggiero, Associate Professor of Spanish at the University of Memphis, draws on her over 10 years of experience designing and teaching Spanish as a world language for specific purposes (WLSP) in American higher education. Though Spanish in the US is the context within which she works, the book is intentionally written to be applicable to the teaching of all WLSPs and not just in the US context of higher education. The book also sets out to be useful to foreign languages instructors of all backgrounds that already have a foundation in language teaching in general and encourages them to build their own WLSP courses using their unique strengths and perspectives. Chapters 1-4 provide context for teaching WLSP, addressing issues such as the definition, scope, and benefits of WLSP, as well as preparation to teach WLSP. Chapters 5-11 address curricular development in community service learning (CSL), to which the author devotes considerable attention, the integration of WLSP into foreign languages classes, interpreting, culture, heritage language learners, and WSLSP during COVID-19. Lastly, the book concludes with a collection of teaching materials appendices ranging from specific online and print resources to a sample syllabus, lesson plans, assignments, and assessments.